DIRÂSAH TAHLÎLIYYAH TAQWÎMIYYAH ‘AN AL-MUFRADÂT FÎ KITÂB MANÂN AL-AZÎZ - Buska, Wahyudi; Prihartini, Yogia; Hasnah, Nur (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
The fundamental problem in this research was how relevant the vocabulary in Arabic book Manan al-Aziz is to a higher level in Indonesia. This study amis to: (1) find out the vocabulary in Manan Aziz's book in terms of number, type, position and method, and (2) know the advantages and disadvantages of the book of Manan Aziz. This was a library research employing evaluation analysis method. Data sources were: The Arabic Teaching Book used for grades 10, 11 and 12 in secondary schools in Indonesia, written by Manan Al Aziz in 2009. The results of this study were: new vocabulary in Manan Aziz book after less repetition (53 words) means 693 vocabularies. The number of vocabularies that must be taught to Arabic for speakers of other languages were 1500/2000 words for advanced level, starting with a large number of words in class eleven is 302 words, then in the twelfth line means 242 words